Differentiation of adipose derived stem cells to keratinocyte-like cells on an advanced collagen wound matrix. (August 2018) - Edwards, N.J.; Stone, R.; Christy, R.; Zhang, C.K.; Pollok, B.; Cheng, X.
Graphical abstract: Highlights: Electrochemically deposited collagen matrices are well suited for wound dressings. The matrices are biocompatible, porous, and posses high tensile strength. hADSCs on matrices co-cultured with keratinocytes exhibit cobblestone morphology. This cellular construct is an innovative and promising treatment for skin injuries. Abstract: Despite advances in tissue engineering and regenerative medicine, skin regeneration and cutaneous wound healing remains a significant medical challenge. A bioengineered skin that stimulates the body's natural regeneration capability is needed to address the current lack of treatment options. To this end, a biocompatible collagen wound matrix was developed using an electrochemical deposition fabrication process. The advanced collagen wound matrix has relatively high tensile strength compared to normal collagen matrix made by the heat gelation process and open porosity, and serves as an excellent platform for cellular growth and differentiation. Human adipose derived stem cells (hADSCs) were cultured on this collagen matrix and a co-culture system with primary keratinocytes and keratinocyte conditioned media was developed for differentiation of the hADSCs to keratinocyte-like cells. After fifteen days, hADSCs in co-culture began to exhibit a "cobblestone-like" morphology, indicating preliminary signs of differentiation to a keratinocyte-like cell. Based on morphological analysis at day 30, the co-culture with keratinocyte conditioned media system shows promising preliminary evidence of hADSC differentiation to a keratinocyte-like cell on an electrochemically aligned collagen wound matrix.